PERANAN MAHASISWA SEBAGAI BENTUK IMPLEMENTASI AKSI PENCEGAHAN KORUPSI - Sintia Rahmadila; Muhammad Rian; Fareel Ridho Agustian (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
Corruption remains a major obstacle in realizing clean and integrity-based governance. Efforts to prevent corruption require the involvement of all elements of society, including students as the younger generation who have a strategic role as agents of change. This article aims to analyze the role of students as a form of implementing anti-corruption actions in social and academic life. The method used is a literature study by reviewing various relevant sources related to student anti-corruption movements. The findings show that students can contribute through strengthening integrity values, practicing honesty in academic activities, participating in organizations that uphold transparency, as well as conducting education and anti-corruption campaigns to the public. In addition, the use of digital media serves as an effective means to expand the reach of anti-corruption movements. Thus, the role of students in implementing anti-corruption actions holds an important position in building a sustainable anti-corruption culture in society.